Threat Modeling Based on a Design Basis Threat for Nuclear Security - Abu Zafor Mohammad Salahuddin; Altab Hossain; Mohammad Shawkat Akbar (International Journal of Nuclear Security, 2024)
Identification of the design basis threat (DBT) of a nuclear facility is an important factor of overall safety, for which the operator is mainly responsible per the guidelines of the International Atomic Energy Agency. As threat levels increase especially threats beyond the DBT-the responsibility of the state also increases. In recent years, only a few studies on nuclear security and DBTs have comprehensively detailed the full spectrum of nuclear facilities in a nation. Thus, this paper presents the correlation between an actual threat and the DBT. The objectives of the study are to assist in establishing physical protection system (PPS) standards that present risks to a nuclear facility, and to determine the level of protection. According to current threat patterns, 34 types of possible and perceivable threat events were identified for DBT in this study. A threat matrix was developed after compiling the assessed threat grades, and this matrix can be a design basis for developing a PPS for any nuclear facility and its security. The DBT study revealed that based on threat variables, each threat in the matrix has a translated representation of threat grades of high, medium, or low. To achieve precision using the deterministic approach, a new seven-step sliding scale for nuclear security events was created, ranging from 0 to 100. The identified threat levels are very low (1–10), low (11–30), moderate (31–50), high (51–60), very high (61–70), severe (71–90), and extreme (91–100). In conclusion, this study revealed that rigorous analysis and decision-making are essential to transforming the threat assessment for the DBT.
Keywords: Design basis threat; nuclear security; threat matrix; risks; threat assessment